Savings box with real-time monitoring and notification for enhanced user experience - Sulaiman, Siti Fatimah; Khor, Jia Yong; Samsudin, Sharatul Izah; Khamil, Khairun Nisa; Sulaiman, Noor Asyikin (Penerbit Universiti Teknikal Malaysia Melaka, 2025)
A savings box is traditionally used to store money, but manual counting can lead to errors, especially for those with colour blindness who may struggle to distinguish banknote denominations. To solve this, the "My Smart Savings Box" was developed. It automatically calculates and displays the total amount using a NodeMCU ESP32 microcontroller, with a colour sensor for banknotes and an infrared (IR) sensors for coins. Integrated with Internet of Things (IoT), the system sends notifications via email and a mobile app when the box is accessed, providing accurate counting and secure, wireless monitoring. This project enhances money management by minimizing errors and improving convenience.